Integrating Acceptance and Commitment Therapy (ACT) with Psychological Skills Training (PST): a case study - Wood, Samuel; Turner, Martin James (Frontiers in Psychology, 2025)
This case study outlines the sport psychology service delivery provided to an 11-year-old competitive figure skater. The client reported performance anxiety, which hindered her training and performance at competition. The intervention delivered integrated core processes of acceptance and commitment therapy (ACT) with psychological skills training (PST) with the aim of reducing the client’s performance anxiety. Little has been written about how ACT can be applied alongside PST. The case reports how ACT exercises aimed at defusing the client’s unhelpful cognitions, focusing on valued living, committed action, and staying in the present moment were integrated into goal setting, imagery, performance profiling, and self-talk. Demonstrating the alignment between ACT and PST is crucial for practitioners to seamlessly integrate ACT into their practice. Reflections from the client and practitioner capture the evaluation of the service delivery.